<h3>
Answer: x + y = 2</h3>
====================================================
Work Shown:
y - 6 = -(x + 4)
y - 6 = -x - 4
y = -x - 4 + 6 ..... adding 6 to both sides
y = -x + 2
y + x = 2 .... adding x to both sides
x + y = 2
The equation is in standard form Ax+By = C, with A = 1, B = 1, and C = 2.
3 (-2)^2 -5 (3)+8
3 (4)-5 (3)+8
12-15+8
-3+8=5
Hope this helps :)
C, if the function rule is x + 1
Step-by-step explanation:
18/24>20/24 you have to flip the sign to make it correct
Answer:
B. Function F is odd
Step-by-step explanation:
If a function is odd, then -f(x) = f(-x), for all values of x.
For such function an origin symmetry is obtained just like the image uploaded.
Also, for such function, there is an equal distance between f(x) and f(-x), just like the image uploaded (d₁ = d₂).
Thus, the correct option is "B"